Application of One-Dimensional Hydrodynamic Model in Water Storage at the End of Flood Seasons for Changzhou Reservoir - LIAO Xiaolong; ZHONG Yixuan; HOU Guibing; JIN Gaoyang (Renmin Zhujiang)
Scientific selection of the timing and time for pre-discharge is one of the key techniques and decision bases necessary for conducting reservoir pre-storage at the end of flood seasons.For channel reservoirs,the water level decline in the reservoir area usually lags behind that at the dam sites,which must be fully considered to avoid the submerging loss of the reservoir area and the increase in flood risks for downstream areas due to untimely pre-discharge.In this research,with the mainstream of Xijiang River,Changzhou hydro-junction,as the research object,a one-dimensional hydrodynamic model is built on the basis of the measured data of river sections in the Changzhou reservoir area to study the effects of water storage at the end of flood seasons.The model parameters are calibrated and validated using observed flood data.The results reveal that pre-discharge should be executed for the Changzhou reservoir to the water level of 18.6 m when the inflow forecast within 3 d exceeds 11 800 m3/s,and a rising water regime is expected.It takes 2.6 d,3.2 d,and 3.7 d for the pool level to be lowered to 18.6 m from 19.6 m,20.1 m,and 20.6 m,respectively,which is about 1.3~2.3 d earlier than the time needed for the reservoir water level to lower to the corresponding water levels.The study provides a useful technical reference for the optimization of water storage at the end of flood seasons in the Changzhou hydro-junction and also lays a scientific foundation for determining the pre-discharge timing and time of channel reservoirs.